2018
DOI: 10.1002/adma.201801984
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer‐Spacing‐Regulated VOPO4 Nanosheets with Fast Kinetics for High‐Capacity and Durable Rechargeable Magnesium Batteries

Abstract: Owing to the low-cost, safety, dendrite-free formation, and two-electron redox properties of magnesium (Mg), rechargeable Mg batteries are considered as promising next-generation secondary batteries with high specific capacity and energy density. However, the clumsy Mg with high polarity inclines to sluggish Mg insertion/deinsertion, leading to inadequate reversible capacity and rate performance. Herein, 2D VOPO nanosheets with expanded interlayer spacing (1.42 nm) are prepared and applied in rechargeable magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(132 citation statements)
references
References 34 publications
3
129
0
Order By: Relevance
“…The medium bind energy difference suggests the coexistence of Mn 4+ and Mn 3+ in lithiated Li 4 Mn 5 O 12 . The partial Mn 4+ in fully discharged Li 4 Mn 5 O 12 is related with the non‐equilibrium state of the active material during the cycling and the Li + diffusivity is not fast enough to the occurrence of adequately electrochemical reaction on the whole electrode, commonly found in other experiments . After the subsequent charge to 2.7 V (vs. Mg 2+ /Mg), the delithiated Li 4+x Mn 5 O 12 displays two peaks of Mn 2p 3/2 and Mn 2p 1/2 centered at 642.2 eV and 653.9 eV, respectively.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The medium bind energy difference suggests the coexistence of Mn 4+ and Mn 3+ in lithiated Li 4 Mn 5 O 12 . The partial Mn 4+ in fully discharged Li 4 Mn 5 O 12 is related with the non‐equilibrium state of the active material during the cycling and the Li + diffusivity is not fast enough to the occurrence of adequately electrochemical reaction on the whole electrode, commonly found in other experiments . After the subsequent charge to 2.7 V (vs. Mg 2+ /Mg), the delithiated Li 4+x Mn 5 O 12 displays two peaks of Mn 2p 3/2 and Mn 2p 1/2 centered at 642.2 eV and 653.9 eV, respectively.…”
Section: Resultsmentioning
confidence: 74%
“…[49] The partial Mn 4 + in fully discharged Li 4 Mn 5 O 12 is related with the non-equilibrium state of the active material during the cycling and the Li + diffusivity is not fast enough to the occurrence of adequately electrochemical reaction on the whole electrode, commonly found in other experiments. [64] After the subsequent charge to 2. Figure S12 shows the ex-situ XRD patterns of Li 4 Mn 5 O 12 electrodes in various states.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…But it was found that pristine VOPO 4 showed poor Mg 2+ storage performance, and the special modifications are necessary. Zhou et al effectively expanded the interlayer spacing of VOPO 4 · 2H 2 O from 0.74 to 1.42 nm by phenylamine molecules preintercalation. The enlarged layer spacing results in the fast diffusion kinetics of MgCl + ions with low polarization.…”
Section: Vanadium Phosphatesmentioning
confidence: 99%
“…A small amount of H 2 O is then generally used in the cathode reaction to shield the divalent Mg 2 + charge by hydration, facilitating the insertion and removal of Mg 2 + ions into/from the oxide cathode to obtain improved cyclability. [94,116,117] However, as discussed in the previous section, H 2 O is not compatible with the anode, and will cause the formation of a passivation layer. Thus, although they provide a higher operating voltage, the use of these transition-metal oxides is still limited.…”
Section: Transition-metal Compoundsmentioning
confidence: 99%